PEMILIHAN UKURAN KINERJA BERDASARKAN KARAKTERISTIK PEKERJAAN, PERSAINGAN PASAR, DAN TUJUAN STRATEGIS PERUSAHAAN EKSPEDISI - Elsa Meirina; Mike Kusuma Dewi (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2022)
This research is a type of quantitative research in which researchers look at the performance measures of several shipping companies in the city of Padang based on job characteristics, market competition, and company strategic goals. The research data used in the form of distributing questionnaires to expedition employees in the city of Padang. All data were processed using multiple regression analysis by looking at the validity, reliability, classical assumptions, descriptive analysis and hypothesis testing with T test and R2 test. The variables in this study are job characteristics, with the results having no effect on performance measures for expedition employees in the city of Padang (H1) due to differences in the characteristics of research work, culture, conditions and work situations where the research was conducted with previous studies, while market competition (H2) and the company's strategic objectives (H3) have a positive effect on the size of the company's performance.